A scoping review of privacy and utility metrics in medical synthetic data - Bayrem Kaabachi; Jérémie Despraz; Thierry Meurers; Karen Otte; Mehmed Halilovic; Bogdan Kulynych; Fabian Prasser; Jean Louis Raisaro (npj Digital Medicine)
Abstract The use of synthetic data is a promising solution to facilitate the sharing and reuse of health-related data beyond its initial collection while addressing privacy concerns. However, there is still no consensus on a standardized approach for systematically evaluating the privacy and utility of synthetic data, impeding its broader adoption. In this work, we present a comprehensive review and systematization of current methods for evaluating synthetic health-related data, focusing on both privacy and utility aspects. Our findings suggest that there are a variety of methods for assessing the utility of synthetic data, but no consensus on which method is optimal in which scenario. Moreover, we found that most studies included in this review do not evaluate the privacy protection provided by synthetic data, and those that do often significantly underestimate the risks.